1998
DOI: 10.1128/jvi.72.3.1983-1993.1998
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid and Matrix Protein Contributions to Selective Human Immunodeficiency Virus Type 1 Genomic RNA Packaging

Abstract: The nucleocapsid protein (NC) of retroviruses plays a major role in genomic RNA packaging, and some evidence has implicated the matrix protein (MA) of certain retroviruses in viral RNA binding. To further investigate the role of NC in the selective recognition of genomic viral RNA and to address the potential contribution of MA in this process, we constructed chimeric and deletion human immunodeficiency virus type 1 (HIV-1) mutants that alter the NC or MA protein. Both HIV and mouse mammary tumor virus (MMTV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…As shown in Figure 6, the level of MAII particle-associated RNA was roughly comparable to that of WT when normalized for the Gag protein level. Results from RT-PCR experiments (data not shown) by using gagspecific primers [Poon et al, 1998] also support the conclusion that the MAII mutation has no significant effects on RNA incorporation.…”
Section: Viral Rna Contentsmentioning
confidence: 56%
See 1 more Smart Citation
“…As shown in Figure 6, the level of MAII particle-associated RNA was roughly comparable to that of WT when normalized for the Gag protein level. Results from RT-PCR experiments (data not shown) by using gagspecific primers [Poon et al, 1998] also support the conclusion that the MAII mutation has no significant effects on RNA incorporation.…”
Section: Viral Rna Contentsmentioning
confidence: 56%
“…Although a number of studies have shown that the HIV MA domain is not required for incorporating viral RNA into particles Reicin et al, 1995;Poon et al, 1998], we examined genomic viral RNA of MAII particles by the slot-blot experiment as described in Materials and Methods. Aliquots of the identical medium pelleted samples were also analyzed for Gag proteins by Western immunoblotting.…”
Section: Viral Rna Contentsmentioning
confidence: 99%
“…The NC domain is responsible for nonreciprocal RNA packaging of MLV and SNV. Several chimeras of Gag containing NC from different viruses have been previously tested, and mixed results were obtained (2,14,28,45,58). For example, chimeric HIV-1 Gag with MLV NC preferentially packaged MLV RNA (2, 58), but chimeric HIV-1 Gag with MMTV NC still preferentially packaged HIV-1 RNA (45).…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicated that NC is, at least in part, responsible for RNA packaging specificity. In contrast, the chimeric HIV-1 Gag containing NC derived from mouse mammary tumor virus (MMTV) still preferentially packaged HIV-1 RNA (45). This observation indicated that replacement of the NC was not sufficient to alter the packaging specificity and that other Gag domains were involved.…”
mentioning
confidence: 99%
“…Retroviral gag apparently possesses all required signals for VLP assembly and budding, and functional domains involved in coronavirus VLP assembly and budding are allocated throughout the M, E, and N proteins. Despite being completely unrelated, the SARS-CoV N protein and HIV-1 NC have similar properties: both contain putative proteinprotein interaction domains and both play roles in viral RNA packaging [4,5,18,32,33,53]. A domain responsible for Gag-Gag interactions (referred to as an I domain) has been mapped to HIV-1 NC [3,7].…”
Section: Introductionmentioning
confidence: 99%